Pendampingan Praktik Pengajaran Tafsir Jalalain di Himpunan Mahasiswa Lembata (HIMALE) Bogor - Syaeful Rokim; Aceng Zakaria; Herman (LPPM STAI Muhammadiyah Probolinggo, 2026)
This community service program aimed to enhance the understanding of Qur’anic interpretation among members of the Lembata Student Association (HIMALE) in Bogor through mentoring in the practical teaching of Tafsir Jalalain. The program employed a qualitative descriptive-participatory approach and was conducted through a series of activities, including public lectures, thematic sermons, group discussions, interactive question-and-answer sessions, and participant-led tafsir presentation practices. Data were collected through direct observation, field notes, participant reflections, and documentation, then analyzed descriptively to evaluate the effectiveness of the mentoring process. The results indicated an improvement in participants’ basic knowledge of tafsir, their ability to relate Qur’anic verses to everyday life, and increased confidence in explaining the meanings of verses using the simple and concise style of Tafsir Jalalain. In addition, the program strengthened religious learning culture and Islamic brotherhood within the organization. These findings suggest that Tafsir Jalalain is an appropriate introductory reference for Qur’anic interpretation learning among university students with diverse religious backgrounds, although further sustainable and long-term mentoring programs are recommended to achieve deeper and more systematic tafsir studies.